Mulheres na gestão das IFES: uma análise sobre a perspectiva de gênero no espaço organizacional da Universidade Federal do Tocantins - UFT - Lopes, Suely Pereira (Universidade Federal do Tocantins, 2023)
This study intends to contribute to the discussion on the gender perspectives of women and men holding management positions at Federal Institutions of Higher Education (FIHE), having the Federal University of Tocantins (UFT) as an analytical focus. In this sense, the research deals with gender perspectives in a given sociocultural context and seeks to dialogue with feminist epistemologies. The objective is to analyze how the women that holding management positions such as Rector and Pro-Rector of the UFT put gender perspectives in their practices. The question that guides this study is: how and if the women who occupied management positions in the upper administration of the UFT put gender perspectives in their practices? For that, we carried out a case study of a qualitative nature based on the methodology of Oral History. Thus, the theoretical-methodological framework chosen for this study seeks to understand gender perspectives in the organizational space, considering the life stories, personal experiences of women and men who occupied management positions at UFT. Oral history is important for this research, as it brings narratives of women and men with an interpretation of the present together with memories of the past. Thus, this work contributes to gender studies in spaces of power and decision-making within the university. This work intends the narratives of women and men, however, the women's speeches are highlighted, in view of the position they are in society and the path taken. The time frame was 2003-2021 covering a period of eighteen years, a period chosen due to the process of creation and expansion of the university and has as interlocutors the seven women who held the position of pro-rector and three men who held the position of rector of the aforementioned Institution. The relevance of this study lies in presenting the social and professional reality experienced by women who acted and act in conducting the UFT. In addition, it seeks to awaken the interest of other researchers in the continuity of investigations of gender perspectives in the Brazilian federal universities, contributing to the theme in the contemporary world, where the creation of new epistemes on old themes stands out. It was concluded, given the narratives presented, that the interlocutors of the research showed that they did not have a theoretical notion of the gender perspective, so they do not operationalize it in management. In this way, it is related to the structure and also to the individual possibilities. Although the interlocutors have not mobilized the gender perspective in their management, their presence in this space of power is a reflection of changes. It was noted that the upper management environment at UFT is still not favorable to the entry of other women, being predominantly occupied by men. Finally, it is necessary for more women to occupy spaces of power so that our claims can be made explicit, recognized and contemplated with gender equity. Equal opportunities for men and women and the equality of women with men in occupying positions in spaces of power are necessary. In this way, we hope that this study will broaden the debate on the presence of women in strategic positions in the Brazilian public institutions